Orthosiphon stamineus Benth. impedes carbon tetrachloride-induced hepatic damage by modulating oxidative stress - Muhammad Dawood Shah; Mohammad Amil Zulhilmi Benjamin; Mohammad Iqbal (The Official Publication of the Malaysian Society for Biochemistry & Molecular Biology, 2024)
Orthosiphon stamineus Benth. (Lamiaceae) is an herb traditionally used in folk medicine for protecting against various diseases such as oxidative stress. This study aimed to assess the antioxidant and hepatoprotective properties of the ethanol extract of O. stamineus (EEOS) in rats with hepatic injury induced by carbon tetrachloride (CCl4). The antioxidant properties of EEOS were evaluated through total phenolic content (TPC), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) and reducing power assays. Sprague-Dawley rats were orally administered EEOS at doses of 100, 500, and 1000 mg/kg b.wt. for two weeks, followed by exposure to CCl4 (1.2 mL/kg). The rats were then euthanised for biochemical analyses. In vitro studies demonstrated the robust antioxidant potential of EEOS, revealing effective scavenging of DPPH free radicals and reducing power. Additionally, EEOS exhibited a high TPC of 127.28 ± 1.57 mg GAE/g db, contributing significantly to its antioxidant activities. Administration of EEOS significantly mitigated CCl4-induced toxicity, as evidenced by reduced alanine transaminase (1–91-fold recovery) and aspartate transaminase (1–28-fold recovery) levels of hepatic damage in rats. Moreover, EEOS alleviated the heightened malondialdehyde levels (40–80% recovery) and elevated reduced glutathione levels (30–80% recovery) in CCl4-induced rats, while also restoring levels of various antioxidant enzymes: catalase (12–20% recovery), glutathione peroxidase (23–41% recovery), glutathione reductase (6–30% recovery), glutathione S-transferase (11–25% recovery), and quinone reductase (8– 35% recovery). The study conclusively demonstrates the strong antioxidant potential of EEOS, with 1000 mg/kg b. wt. exhibiting efficacy in restoring antioxidant enzymes. These compelling findings highlight the potential of EEOS as a promising candidate for preventing liver damage associated with reactive oxygen species.